MINTY ALLEY - James, C. L. R. (Cyril Lionel Robert), 1901-1989; Evaristo, Bernardine, 1959- (London : Penguin Books, 2021)
"It is the 1920s in the Trinidadian capital, and Haynes' world has been upended. His mother has passed away, and his carefully mapped-out future of gleaming opportunity has disappeared with her. Unable to afford his former life, he finds himself moving into Minty Alley - a bustling barrack yard teeming with energy and a spectacular cast of characters. In this sliver of West Indian working-class society, outrageous love affairs and passionate arguments are a daily fixture, and Haynes begins to slip from curious observer to the heart of the action."
Keywords: Reacher, Jack, -- (Fictitious character) -- Fiction; Nineteen twenties -- Fiction; Life change events -- Fiction; Social classes -- Fiction; Interpersonal relations -- Fiction; West Indies -- Social life and customs -- Fiction; Domestic fiction